Meʿmārbāshis of the Nasirid Court (1848- 1896) - Hamid Reza Pishvaei; Zahra Ahari (صفه)
The Qajar period, especially the times of Nasir al-Din Shah’s reign (1848- 1896), is a critical period, and in a sense is the beginning for the modern era in the history of contemporary architecture in Iran. However, there is not a clear picture of how architects worked in this period. Despite the abundance of documents about the ‘meʿmārbāshis’ of the Nasirid court remained from that time, we know little about seminal guild at the court. Employing a historical approach, the present paper aims to study meʿmārbāshis of the Nasirid court’s works and lives, duties and responsibilities, and the evolution of the position ‘meʿmārbāshi’ in this period. Written documents of the period indicate that five people held the position ‘meʿmārbāshi’ during the Nasirid period: ʿAbd Allāh Khān, Mohammad Taghi Khān, Mohammad Ebrāhim Khān, Hāji Abol-Hasan, and Hosein ʿAli Khān the meʿmārbāshis. They had a diverse series of duties and responsibilities, but their main remit was to manage technical affairs related to the whole royal constructions at the same time. The increasing number of royal constructions during 1866- 1883 resulted in the formation of the ‘chief-mason’ role and the increasing power of senior architects. The consequences eventuated a rotation in the position of meʿmārbāshi and, after several years of interruption, led it to be possessed by expert architects again. With the development of bureaucracy came a clarification of labour division between the meʿmārbāshi and holders of other roles and positions. These changes could be considered as a sign of modernity in the professional architecture organisations of the Nasirid court.